THE EFFECT OF EDUCATION LEVEL AND ACCESS TO INFORMATION ON PUBLIC PARTICIPATION IN THE 2014 ELECTION IN MAKASSAR CITY - andi triwenni wulandari tenri; Ibrahim; Hasruddin Nur (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the effect of education level and access to information on community participation in the 2024 General Election in Makassar City. This research employs a quantitative approach using a survey method. The population consists of residents in Tamalanrea, Biringkanaya, Bontoala, and Tallo Districts, with a sample of 81 respondents selected using the Slovin formula. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression analysis. The results indicate that education level has a significant effect on community participation in the 2024 General Election, as evidenced by a t-test significance value of 0.003. Access to information also shows a significant effect on community participation, with a t-test significance value of 0.000. Simultaneously, education level and access to information significantly influence community participation, as indicated by the F-test significance value of 0.000. The coefficient of determination (R Square) of 0.438 shows that education level and access to information explain 43.8% of the variation in community participation, while the remaining 56.2% is influenced by other factors outside the research model. Based on these findings, it can be concluded that improving the quality of education and ensuring equitable access to information play an important role in encouraging more active and meaningful community participation in democratic processes, particularly in general elections.